PARASITOLOGICAL ANALYSIS OF Lactuca sativa CULTIVATED WITH DIFFERENT ORGANIC FERTILIZERS - NAKASHIMA, HIGOR HISASHI; FAGLIONI, CAROLINE MENDES; AGUERA, RAUL GOMES; SANTOS, RENAN UHDRE; ECKER, ARNEY EDUARDO DO AMARAL; ECKER, ALESSANDRA BARROCHELLI DA SILVA (Uningá Review, 2019)
Lettuce is commonly consumed in Brazil. It is mainly eaten in natura, and this is the reason why it is a vehicle of parasitic contamination. The objective of this work was to evaluate the parasitic contamination of three different organic fertilizers - filter cake (TF), manipueira (MA), and agricultural byproduct (RA) -, in Lactuca sativa cv. Valentina samples, using the following applications: TF/T1: no fertilizer, TF/T2: 3.6kg/m², and TF/T3: 7.2kg/m²; MA/T1: no fertilizer, MA/T2: 4.32L/m², and MA/T3: 8.64L/m²; and RA/T1: no fertilizer, RA /T2: 3.6 kg / m², and RA/T3: 7.2 kg/m². The leaves and capsules used in the research were washed with a 0.5% neutral detergent solution and these samples were subjected to Hoffman’s and Faust’s methods. The results of the analyses demonstrated that 100% of the samples were contaminated with Ancilostomydae larvae regardless of the fertilizer or concentration used. Ancilostomydae larvae were only found with the following specifications: TF/T1 (83.33%), TF/T2 (66.66%), TF/T3 (50%), MA/T1 (66.66%), MA/T2 (83.33%), MA/T3 (33.33%), RA/T1 (80%), RA/T2 (60%), and RA/T3 (40.00%). Ancilostomydae larvae associated with Ancilostomydae eggs were found with TF/T1 (0%), TF/T2 (16.66%), TF/T3 (0%), MA/T1 (16.66%), MA/T2 (0%), MA/T3 (0%), RA/T1 (0%), RA/T2 (0%), and RA/T3 (0%). And Ancilostomydae larvae associated with Taenia eggs were found with TF/T1 (16.66%) TF/T2 (16.66%), TF/T3 (50%), MA/T1 (16.66%), MA/T2 (16.66%), MA/T3 (66.66%), RA/T1 (20%), RA/T2 (40%), and RA/T3 (60%). Considering the research results, we reinforce the need for sanitizing and controlling the means of contamination in vegetables grown for sale and consumed in natura to prevent parasitic infection in consumers.